Indie craft - Waterhouse, Jo (London : Laurence King, 2010)
Showcases the Indie Craft or DIY craft. This title includes tattoo-influenced tapestry/needlepoint, graffiti cross-stitching, cross-stitching on to metal, 3D embroidery, and knitted street art. It is of interest to the craft community, art, design and textile students, and those who enjoy craft-based art.
boek